El uso de las fuentes escritas en la enseñanza de la Historia. Análisis de textos escolares para tercero y cuarto de secundaria - Valle Taiman, Augusta (Pontificia Universidad Católica del Perú, 2011)
The use of written sources for teaching History. Analysis of textbooks for thethird and fourth years of high schoolCurrently, in addition to the usual contents, history textbooks now cite primary and secondary sources with suggested activities. This research analyzes these proposed activities in history textbooks for third- and fourth-year students. The objective is to evaluate the degree to which the activities proposed in the sourcespromote the development of critical thought in students.Students exercise critical thought when they engage in the activities suggested in the sources cited to compare different versions of the same historical events and then process this new information to develop their own response to a historical problem. This level of complexity is not achieved in most of the suggested activities given that sources tend to serve only to supplement information